Self‐facilitation and negative species interactions could drive microscale vegetation mosaic in a floating fen. (27th February 2020) - van Bergen, Tamara J. H. M.; Temmink, Ralph J. M.; van Tweel‐Groot, Loekie; Bakker, Wiene J.; Rehlmeyer, Katrin; Koks, Adam H. W.; Waajen, Annemiek C.; Roelofs, Jan G. M.; Grootjans, Albert P.; van der Heide, Tjisse; Lamers, Leon P. M.
Abstract: Aim: The formation of a local vegetation mosaic may be attributed to local variation in abiotic environmental conditions. Recent research, however, indicates that self‐facilitating organisms and negative species interactions may be a driving factor. In this study, we explore whether heterogeneous geohydrological conditions or vegetation feedbacks and interactions could be responsible for a vegetation mosaic of rich and poor fen species. Location: Lake Aturtaun, Roundstone Bog, Ireland. Methods: In a floating fen, transects were set out to analyze the relation between vegetation type and rock–peat distance and porewater electrical conductivity. Furthermore, three distinct vegetation types were studied: rich fen, poor fen and patches of poor fen within rich fen vegetation . Biogeochemical measurements were conducted in a vertical profile to distinguish abiotic conditions of distinct vegetation types. Results: Geohydrological conditions may drive the distribution of poor and rich fen species at a larger scale in the floating fen, due to the supply of minerotrophic groundwater. Interestingly, both rich and poor fen vegetation occurred in a mosaic, when electrical conductivity values at 50 cm depth were between 300 µS/cm and 450 µS/cm. Although environmental conditions were homogeneous at 50 cm, they differed markedly between rich and poor fen vegetation at 10 cm depth. Specifically, our measurements indicate that poor fen vegetation lowered porewater alkalinity, bicarbonate concentrations and pH. No effects of rich fen vegetation at 10 cm depth on biogeochemistry was measured. However, rich fen litter had a higher mineralization rate than poor fen litter, which increases the influence of minerotrophic water in rich fen habitat. Conclusions: These results strengthen our hypothesis that species can drive formation of vegetation mosaics under environmentally homogeneous conditions in a floating fen. Positive intraspecific self‐facilitating mechanisms and negative species interactions could be responsible for a stable coexistence of species, even leading to local ecosystem engineering by the species, explaining the local vegetation mosaic at the microscale level in a floating fen. Abstract : A stable mosaic of rich and poor fen vegetation in a floating fen with homogeneous geohydrological conditions was likely driven by vegetation feedbacks and negative species interactions. Biogeochemical conditions only differed between vegetation types in the upper peat layer. These results strengthen our hypothesis that poor fen species invade during a window of opportunity, causing species to drive vegetation mosaics.